Performance evaluation of paraffin wax as phase change material in a horizontal cylindrical thermal energy storage unit - Ali, Shahid; Deshmukh, Suresh Pandurang; Mohamad, Ahmad Tajuddin; Warimani, Mahammadsalman; Khan, Sher Afghan (Semarak Ilmu Publishing, 2025)
Fossil fuels like coal, oil, and natural gas currently dominate global energy production but release significant amounts of CO2 and other greenhouse gases, contributing to global warming and climate change. To address these environmental concerns, alternative methods of energy production and storage must be explored. This study investigates the thermal performance of latent heat thermal energy storage (LHTES) using phase-change materials (PCMs) in a horizontal cylinder. The experimental setup consists of a copper tube, 650 mm in length, with an inner diameter of 25 mm and a thickness of 2 mm, enclosed by a 600 mm acrylic tube with a diameter of 45 mm and thickness of 5 mm, and insulated to minimize heat loss. The temperature distribution was monitored along the axial direction during charging and discharging processes. These findings suggest that the proposed method can enhance the efficiency and performance of thermal energy storage systems, making them more suitable for practical applications in renewable energy storage